Models and realization of intrusion detection in enterprise corporate information system with intellectual approuch - U. A. Vishniakou; M. G. Mosdurany Shiras (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The methodic of intrusion detection in corporate information systems (CIS) on three levels are done. Models of autonomic and net intrusion detection systems (IDS) including some components are presented. IDS on the base of Snort is worked out and used. During its investigation some tasks were executed: creating the virtual computer net for CIS, analyzing its possible vulnerability; attuning and preparing IDS for CIS with intellectual approach (knowledge in rules view); checking of IDS activity during simulation various attacks and their detection.